PELAKSANAAN PEWARISAN HARTA PUSAKA TINGGI MINANGKABAU DI NAGARI KOTO NAN GADANG KOTA PAYAKUMBUH DIHUBUNGKAN DENGAN FALSAFAH ADAT BASANDI SYARA’ SYARA’ BASANDI KITABULLAH - Hannana Fitria (Jurnal Dialektika Hukum, 2025)
Minangkabau is an area in Indonesia where the community can be found regulated based on the mother law or the matrilineal system starting from a small living environment (family) to the highest living environment, namely a nagari. Minangkabau inheritance law is a concrete issue that is still constantly being questioned because on the one hand Minangkabau inheritance law is a continuation in accordance with the order of the arrangement according to the matrilineal law, but on the other hand it is related and influenced by sharia law (religion). The indigenous people of Minangkabau generally adhere to Islam and have hereditary guidelines and provisions that the status of Minangkabau people will be revoked if they are not Muslims. The Minangkabau philosophy which is the fundamental teaching is "adat basandi syara', syara' basandi kitabullah" which means that the prevailing customs or customs in the community such as buying and selling, marriage, inheritance distribution, and others should not contradict what has been shari'a in the Qur'an. However, in practice, in Minangkabau, especially in Nagari Koto Nan Gadang, the implementation of inheritance of property, especially high inheritance, is considered not in accordance with the rules of Islamic sharia and the philosophy of "adat basandi syara', syara' basandi kitabullah" this has become a debate among religious leaders, traditional leaders, intellectual figures and even the Minangkabau people themselves because in Islamic sharia there is no inheritance of property based on the hereditary system according to the mother's line. However, the Minangkabau community itself believes that the inheritance is born from generation to generation from ancestors and inherited based on the mother's lineage. Keywords: Inheritance, High Heirloom Property, Minangkabau